2001
DOI: 10.1209/epl/i2001-00476-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the biasing electric field on aging in potassium niobo-tantalate crystals

Abstract: Aging in the disordered ferroelectric potassium niobo-tantalate has been studied by measuring the real and imaginary parts of the dielectric constant at various frequencies when a biasing electric field is applied. It is found that rejuvenation and memory effects can be induced by the field. The effects of temperature and field are compared and the results are discussed in terms of a model which attributes the time-dependent part of the dielectric constant to growth and reconformation of the polarization domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2003
2003
2006
2006

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…This phenomenon is called aging [1]. It is generally observed in materials which contain some type of disorder [2], such as structural glasses [3], spin-glasses [4] and disordered dielectrics [5].Recently, experiments performed in potassium niobo-tantalate (a disordered dielectric material -KTN in short) showed that a static electric field of amplitude E seems to act as temperature [6,7]: small field changes produce variations of the complex dielectric constant ε(t) opposite to the aging evolution (i.e. rejuvenation), while large back and forth field variations keep partial memory of aging.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon is called aging [1]. It is generally observed in materials which contain some type of disorder [2], such as structural glasses [3], spin-glasses [4] and disordered dielectrics [5].Recently, experiments performed in potassium niobo-tantalate (a disordered dielectric material -KTN in short) showed that a static electric field of amplitude E seems to act as temperature [6,7]: small field changes produce variations of the complex dielectric constant ε(t) opposite to the aging evolution (i.e. rejuvenation), while large back and forth field variations keep partial memory of aging.…”
mentioning
confidence: 99%
“…Recently, experiments performed in potassium niobo-tantalate (a disordered dielectric material -KTN in short) showed that a static electric field of amplitude E seems to act as temperature [6,7]: small field changes produce variations of the complex dielectric constant ε(t) opposite to the aging evolution (i.e. rejuvenation), while large back and forth field variations keep partial memory of aging.…”
mentioning
confidence: 99%